2013
DOI: 10.1177/0956462413480721
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced therapy for primary and secondary syphilis: a longitudinal retrospective analysis of cure rates and associated factors

Abstract: For the treatment of early infectious syphilis, enhanced therapy with three dosages of benzathine penicillin G has been under consideration, particularly in the human immunodeficiency virus type 1 infected population (HIV-1). The serological outcome of 249 patients with primary and secondary syphilis treated with standard or enhanced therapy was analyzed retrospectively; 98% (139/142) achieved serological cure with a single dosage and 92% with enhanced therapy (P=0.033). In HIV-1 infected individuals, cure rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
1
13
3
1
Order By: Relevance
“…Overall, four observational studies not included in the 2011 and 2014 systematic reviews included sample sizes of 62 to 350 subjects and concluded that there were no differences in serologic response at 12 (n=2 or 3 studies) or 24 months (n=1 study) if one or three doses BP-G were given (38)(39)(40)(41). The fifth and largest, observational study conducted to date (n=573) in Taiwan hypothesized that one dose was not inferior to three weekly doses of BP-G and set the significant difference between regimens as 10% of participants with a serologic response at 12 months.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, four observational studies not included in the 2011 and 2014 systematic reviews included sample sizes of 62 to 350 subjects and concluded that there were no differences in serologic response at 12 (n=2 or 3 studies) or 24 months (n=1 study) if one or three doses BP-G were given (38)(39)(40)(41). The fifth and largest, observational study conducted to date (n=573) in Taiwan hypothesized that one dose was not inferior to three weekly doses of BP-G and set the significant difference between regimens as 10% of participants with a serologic response at 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of anti-retroviral therapy is an important characteristic to include when assessing the efficacy of syphilis therapy. Tittes et al found a slower response to one-dose therapy within an HIV-positive group compared to an HIV-negative group, but there was no significant benefit when the two groups were treated with the three-dose regimen (41 1 Number of study participants analyzed and not necessarily the total number of infections 2 Reflects the number of cases as some study subjects contributed more than one infection SYSTEMATIC REVIEW significant association between higher CD4 count and time to response to therapy (38,40).…”
Section: Hiv Statusmentioning
confidence: 99%
See 3 more Smart Citations